Impact of COVID-19 on Mortality in the Canton of Sarajevo in Period 2020-2022 - Abdulahović, Damir; Žilić, Amar (Scripta Medica, 2024)
Background/Aim: Until March 2023, it has been reported over 676 million cases of COVID-19 globally with almost 7 million deaths caused by this disease. Aim of this study was to determine COVID-19-related deaths and to study how COVID-19 pandemic impacted mortality of residents in the Canton of Sarajevo in 2020-2022 time period. Also, aim was to analyse to what extent the number of registered non-COVID-19-related deaths have changed in the Canton of Sarajevo compared to what would have been expected in the absence of the virus to better measure the impact of COVID-19.Methods: This study used mortality data obtained from Federal Institute for Statistics for period 2017-2022. Data was analysed and presented as raw numbers, age-, sex-, cause of death - crude death rates (CDR), excess mortality and P-score.Results: CDR in the Canton of Sarajevo in 2020 was 1246.3 per 100.000 persons, 1488.6 in 2021 and 1153.4 in 2022, while in period from 2017-2019 CDR ranged from 1051.3 to 1057.9. Total CDR in 2020 increased by 18.3 % compared to 2017-2019 average CDR, this relative difference being even greater in 2021 (41.3 %) and lower in 2022 (9.5 %). In 2020-2022 time period, 9 of the 10 leading causes of death remained the same as in 2019. COVID-19 was the 3rd leading cause of death in 2020 and 2022, while in 2021 spiked as the leading cause of death. In 2020 there was increase of 7 % in deaths from non-COVID-19 related deaths compared to mean number of deaths for period 2017-2019. As for 2021, this number goes higher (9.5 %) and in 2022 was much lower (1.0 %). Conclusion: In the Canton of Sarajevo, COVID-19 pandemic made a big impact on mortality in 2020-2022 years period. Data have changed in total mortality, leading causes of death and excess mortality. Deep-rooted organisational weaknesses that were exposed during pandemic that can bring harm to population from preventable chronic diseases needs to be addressed which have impact on morbidity and at the end, on mortality.
Keywords: Mortality; COVID-19; Crude death rate; Excess mortality